1963
DOI: 10.1063/1.1706904
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Instability in the Theta Pinch

Abstract: An experimental study of the rotation and associated instability was made in a theta pinch with a peak field of 85 kG reached in 2.3 μsec. The starting deuterium gas pressure was in the range 50–150 μ Hg, and for operation on the second half-cycle of the sinusoidal driving field the magnetic flux trapped within the plasma varied between ±100 kMx. In most conditions the circular cross section of the plasma became perturbed along its length by the growth of two flutes which rotated at an angular velocity of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…3 It is argued that a radial component of current can occur as a result of electrons drifting to the wall along magnetic field lines and that this torque acts during the radial acceleration period. 4 We have looked for current and magnetic field components that would accompany such a torque mechanism in our flat spiral coil accelerator and have concluded that, for that geometry, such a mechanism is not present. 5 Experiments were carried out in a 0-pinch for the specific purpose of investigating current partition.…”
Section: Introductionmentioning
confidence: 98%
“…3 It is argued that a radial component of current can occur as a result of electrons drifting to the wall along magnetic field lines and that this torque acts during the radial acceleration period. 4 We have looked for current and magnetic field components that would accompany such a torque mechanism in our flat spiral coil accelerator and have concluded that, for that geometry, such a mechanism is not present. 5 Experiments were carried out in a 0-pinch for the specific purpose of investigating current partition.…”
Section: Introductionmentioning
confidence: 98%
“…Bo MHorHX 3KcnepHMeHTajibHbix pa6oxax [1][2][3][4][5][6], nocBameHHiix H3yHeHHio noBe^eHHa njia3Mbi B Mar-HHTHOM nojie Ha6jiK)fl,aJiocb cwjibHoe c^opMbi nepBOHanajibHoro njia3MeHHoro B pe3yjibTaTe pa3BHTH« HeycTOHMHBocTew. HecMOTpa Ha pa3Hoo6pa3ne ycjiOBHM, xapaxTep STMX MCKa>KeHHH B pa,ae cjiynaeB HMeeT MHoro o6m,ero H Bbipa^caeTca B nOHBJieHHH «HMTeil» [7] HJ1M «(j)aKeJ10B» [3], Bbipbl-H3 o6nacTH 3aHHTOH nna3MOH.…”
Section: Bbe/ieimementioning
confidence: 99%
“…The observations reported here were made during the phase following the radial implosion and before the end of the axial contraction. The rotational instability [3], which appears after the axial contraction, will not be considered.…”
Section: H a B Bodin (Culham Laboratory Culham Berkshire England)mentioning
confidence: 99%